Karakter Kreatif : Hal Yang Harus Dilakukan Guru - wiba, wiba wiba (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
The teacher is a professional position that requires special skills as a teacher. . In practice the teacher is required to have some teaching skills and creativity. Being an ideal, creative and innovative teacher is a profession that must be owned by the teacher, the future is determined by the cadres of the nation, while the main responsibility in providing guidance for the next generation is determined by the role of the teacher as an educator, because they directly interact with students in personality formation, experience developing imagination, and making them tough to face the future. Keywords: Creative and innovative thinking.